3D GIS in archaeological excavations: linking documentation with analytic and synthetic workfows - Katsianis , Markos (Journal of Greek Archaeology, 2024)
Over the past two decades 3D GIS has progressively assumed a more significant role in archaeological excavation documentation. Several case studies have experimented with 3D documentation workflows, while concurrent developments in 3D data capture and GIS software have greatly improved their integration into intra-site archeological research. However, there is still much to discover regarding the possibilities of 3D GIS in archaeological excavations. While we have been successful in bringing data to 3D, we still face challenges in using them for stratigraphic analysis, patterning exploration, interpretive work and, ultimately, knowledge building. This contradiction between increased technological adoption and the challenges in transforming digital practice mirrors findings from recent systematic reviews of peer-reviewed publications on GIS applications in archaeology. These reviews highlight a lack of theoretical engagement, an emphasis on visualization and information management over spatial analysis, difficulties in keeping up with technological advances and education gaps. This is also evident in the Greek context, where the adoption of digital methods varies significantly across the archaeological sector.